An Analysis on Speech Acts in Guy de Maupassant’s Short Story “The Necklace” - Nurvyana Eka Darmananda; Sri Widodo; Abdul Ngafif; Edi Sunjayanto Masykuri (Journal of English Development, 2026)
This study aims to identify and briefly explain the types of speech acts found in the utterances of Guy de Maupassant’s short story “The Necklace.” Using Yule’s speech act theory, 51 utterances were analyzed and classified into representative (22), directive (25), expressive (8), commissive (2), and no declarative speech acts. The classification was based on primary acts supported by secondary or complementary acts reflected in the narration. The findings show that directive and representative speech acts dominate the story, functioning to advance the plot and reveal characters’ experiences and beliefs. Expressive and commissive speech acts occur less frequently because emotions and commitments are mostly conveyed through narrative description rather than dialogue. The results may serve as useful material for EFL instruction, particularly in enhancing reading skills